To simplify the expression \( 18 + 52 - 2(11 - 8)3 \), we'll follow the order of operations (parentheses, exponents, multiplication and division from left to right, addition and subtraction from left to right).
Step 1: Simplify inside the parentheses.
First, calculate \( (11 - 8) \): \[ 11 - 8 = 3. \]
Step 2: Substitute back into the expression.
Now replace \( (11 - 8) \) with \( 3 \): \[ 18 + 52 - 2(3)3. \]
Step 3: Simplify the multiplication.
Next, we simplify \( 2(3)3 \): \[ 2(3)3 = 2 \cdot 3 \cdot 3 = 2 \cdot 9 = 18. \] Now substitute back into the expression: \[ 18 + 52 - 18. \]
Step 4: Perform the addition and subtraction from left to right.
-
Start with \( 18 + 52 \): \[ 18 + 52 = 70. \]
-
Then subtract \( 18 \): \[ 70 - 18 = 52. \]
Final Result:
The simplified expression is \[ \boxed{52}. \]